2019
DOI: 10.3389/fmicb.2019.01354
|View full text |Cite
|
Sign up to set email alerts
|

Tripeptides From Casein Are Signal Molecules to Induce the Expression of the Extracellular Protease MCP-01 Gene in Marine Bacterium Pseudoalteromonas sp. SM9913

Abstract: Microbial extracellular proteases play crucial roles in marine protein degradation and nitrogen recycling. Although a large number of marine bacteria are found to produce extracellular proteases, it is still unknown how marine bacteria respond to environmental proteins to activate the expression of genes encoding extracellular proteases. The inducing signal molecule for marine bacterial extracellular proteases has never been identified. In this study, we identified tripeptides as the inducing signal molecules … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…Four tripeptides, SPP, RYP, RQF, and FRQ, derived from casein have significant inducing effect on the expression of the gene encoding extracellular protease MCP-01 in P. sp. SM9913 (Chen et al 2019).…”
Section: Serine Proteasesmentioning
confidence: 99%
“…Four tripeptides, SPP, RYP, RQF, and FRQ, derived from casein have significant inducing effect on the expression of the gene encoding extracellular protease MCP-01 in P. sp. SM9913 (Chen et al 2019).…”
Section: Serine Proteasesmentioning
confidence: 99%
“…This discovery confirmed that the protein utilized by L. helveticus could stimulate protein translation. A few studies examined how casein influences gene expression during L. helveticus growth ( Chen et al, 2019 ; Zhao et al, 2019 ). However, most of them concluded with analyses of the expression levels of the enzymes involved in bacterial hydrolysis and did not address the changes occurring in transcription or translation.…”
Section: Discussionmentioning
confidence: 99%
“…The expression of mcp01 and production of MCP-01 in strain SM9913 can be induced in the presence of casein but not Casamino Acids, indicating that peptides rather than amino acids derived from casein induce the expression of the gene mcp01 in SM9913. Then, the above-mentioned effective tripeptides were identified from the hydrolysate of casein treated by the ex-proteases of this strain (30). On the other hand, the ex-protease synthesis of Bacillus was reported to be induced by substantially decreased concentrations of amino acids during the exponential growth phase (31,32).…”
Section: Inducers For Microbial Ex-protease Productionmentioning
confidence: 96%